BARRIERS TO TIMELY STROKE CARE - Faris Khairuddin Syah; Putri Ma'rifatul Mardiyah; Isna Imroah Husna; Yanuareza Totti Adyanata; Zahra Roidah Amalia Hasna (Journal of Innovation Research and Knowledge, 2026)
Introduction: Timely treatment is essential in acute ischemic stroke, but prehospital delays often prevent patients from receiving thrombolysis within the therapeutic window. Purpose: This study aimed to identify predictors of delay and explore barriers to prompt stroke care. Methods: A convergent mixed-methods approach was used at a teaching and stroke-ready hospital, involving nine ischemic stroke patients who arrived more than 4.5 hours after symptom onset. Structured questionnaires and semi-structured interviews were conducted, with quantitative data analyzed descriptively and qualitative data thematically. Findings from both methods were integrated using a joint display matrix. Results: All patients arrived after the treatment window, with a median time from onset to hospital of 14 hours. Most participants had low education levels and income, with 56% failing to recognize stroke symptoms and only 22% knowing the ambulance number. Thematic analysis identified four main barriers: symptom misinterpretation, limited stroke awareness, family-centered decision-making, and logistical or systemic obstacles. Discussion: Prehospital delay results from a cascade of personal, social, and systemic factors rather than a single cause. Even with universal health coverage, delays persisted, underscoring the urgent need for community education to improve stroke symptom recognition and for systemic reforms to strengthen emergency care pathways.